14.3: Quantum Dots: Optimizing LCD Systems to Achieve Rec. 2020 Color Performance. Issue 1 (June 2015) - Chen, Jian; Gensler, Steve; Hartlove, Jason; Yurek, Jeff; Lee, Ernie; Thielen, James; Van Derlofske, John; Hillis, James; Benoit, Gilles; Tibbits, Josh; Lathrop, Art
Abstract : Quantum dots have already been adopted in LCDs for higher power efficiency or higher color gamut. In this paper, we report that, by using Quantum Dot Enhancement Film, LCDs are capable of delivering a color gamut that covers more than 90% (CIE 1976) of the Rec. 2020 color gamut, which is the color standard for UHD TV broadcasting.